Association between combined healthy lifestyles and infertility: a cross-sectional study in US reproductive-aged women - Xiaofeng Ye; Xiaoxia Song; Sihang Zhou; Guoqing Chen; Liping Wang (BMC Public Health)
Abstract Background Infertility is a widespread problem for couples worldwide, and lifestyle factors are the cornerstone of infertility prevention. This research seeks to explore the association between combined healthy lifestyles and infertility risk among women of reproductive age. Methods This study analyzed data from the National Health and Nutrition Examination Survey (NHANES, 2013–2018), concentrating on 2,154 women aged 18 to 44. A healthy lifestyle score was created based on healthy diet (top two-fifths of the Healthy Eating Index-2015 score), low-to-moderate alcohol drinking (1–14 g/day), optimal waist circumference (less than 80 cm), adequate physical activity (at least 150 min of moderate-to-vigorous leisure-time exercise per week), and current nonsmoking. Weighted logistic regression analysis was applied to assess the link between healthy lifestyle scores and the risk of infertility, adjusting for potential confounders. Results After adjusting for potential confounders, women exhibiting 4 to 5 healthy lifestyle factors demonstrated a 59% decrease in the likelihood of infertility (OR: 0.41, 95% CI: 0.23–0.76) relative to those with 0 to 1 healthy lifestyle factors. Additionally, each increment in healthy lifestyle factors corresponded to a 21% decrease in infertility risk (OR: 0.79, 95% CI: 0.68–0.92). Analysis of subgroups indicated that the inverse association was more pronounced in females younger than 30. Additionally, optimal waist circumference is the foremost factor contributing to this inverse relationship. Conclusion Adhering to healthy lifestyles significantly lowers the likelihood of infertility among reproductive-aged women. Public health initiatives could consider enhancing access to healthy diets, physical activity, and resources to reduce alcohol consumption and smoking. Further research is required to clarify their relationship and the underlying mechanisms.